The Role of The Contractual Budget in Reducing Financial Waste in Economic Units: Applied research in the Erbil Municipality (Proposed model) - Fian Suleiman Hama Saeed (QALAAI ZANIST JOURNAL, 2023)
The research aims to try to use a modern method in planning and preparing the general budget for the Kurdistan Region - in the presidency of the Erbil municipality, which would have a positive impact on the outputs of the general budget, and thus in reducing financial waste and the public budget in the Kurdistan Region of Iraq is of great importance to the economic units without it It is difficult to determine the size of salaries and wages for the various sectors of society, as well as the inability to provide public services related to health or municipality...etc. And that the preparation of the budget at the present time is based on the traditional method, which in turn leads to the waste of public money, whether in the operational or investment side, and that the best solution to get rid of the ineffectiveness of that budget must be the transition to preparing the budget according to the contractual method of the region in general for the Directorate of Public Retirement in particular Because it is one of the most important public sector departments that provide services through the conclusion of service contracts on the operational side of the budget, as well as partnership contracts with various agencies in the private and mixed sectors. The study reached a set of conclusions, the most important of which is that by shifting towards preparing the budget on a contractual basis, it will help to reduce deviations between what was estimated by the Erbil municipality and the actual amounts allocated to the development projects referred to in the budget. Towards the financial independence of government units in the Kurdistan Region in order to provide services through concluding contracts with entities in the private sector and training the accounting and auditing cadres in government units in general and in the Erbil municipality in particular on the contractual budget preparation mechanism and how to implement it and then evaluate the performance of projects